WiFi, WiMAX, and LTE multi-hop mesh networks : basic communication protocols and application areas - Wei, Hung-Yu; Rykowski, Jarogniew;Dixit, Sudhir (New Jersey : Wiley, 2013)
Wifi, WiMAX, and Cellular Multihop Networks presents an overview of WiFi-based and WiMAX-based multihop relay networks. As the first text to cover IEEE 802. 16j multihop hop relay technology, this revolutionary resource explores the latest advances in multi-hop and ad-hoc networking.
Includes bibliographical references.
Keywords: AD HOC NETWORKS (COMPUTER NETWORKS)